2022
DOI: 10.1007/jhep09(2022)146
|View full text |Cite
|
Sign up to set email alerts
|

Relation between spectra of Narain CFTs and properties of associated boolean functions

Abstract: Recently, the construction of Narain CFT from a certain class of quantum error correcting codes has been discovered. In particular, the spectral gap of Narain CFT corresponds to the binary distance of the code, not the genuine Hamming distance. In this paper, we show that the binary distance is identical to the so-called EPC distance of the boolean function uniquely associated with the quantum code. Therefore, seeking Narain CFT with large spectral gap can be addressed by getting a boolean function with high E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…In short, it is the B-form of the code, and as will be discussed in detail in section 2.2, such a correspondence provides a codetheoretic translation of the simple current orbifold. An interesting aspect of this finding is its connection with our previous paper [Fur22]. We previously found that the CFT spectral gap is in a sense equivalent to the Extended Periodic Criterion (EPC) distance 2 when translated into code theory.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…In short, it is the B-form of the code, and as will be discussed in detail in section 2.2, such a correspondence provides a codetheoretic translation of the simple current orbifold. An interesting aspect of this finding is its connection with our previous paper [Fur22]. We previously found that the CFT spectral gap is in a sense equivalent to the Extended Periodic Criterion (EPC) distance 2 when translated into code theory.…”
Section: Resultssupporting
confidence: 64%
“…In RCFT terminology, this is a map that gives a gluing together of a chiral part and an antichiral part, which is classified using the cohomology of the group. In a previous paper [Fur22], the author introduced the Boolean function f to write the spectral gap ∆ in terms of f and discussed the consideration of f where ∆ is large. Since this KSB can be regarded as a generalization of the Boolean function, we intend to set up a future work to see if in the general RCFT ∆ can be written using KSB.…”
Section: Discussion and Further Directionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also other directions of research related to quantum codes and CFTs [62][63][64][65][66][67][68]. It deserves further investigation to see whether our construction is relevant to these recent developments.…”
Section: Discussionmentioning
confidence: 99%
“…The relation to quantum codes was recently extended and interpreted in terms of CFT Hilbert space in [13]. There are also "bottom-up" generalizations when the connection with codes is perceived as a tool to solve modular bootstrap constraints and construct interesting CFTs [14,15], also see [16,17] for the subsequent developments. In this paper we use this approach and introduce the umbrella construction which generalizes and encompasses the constructions of [14,15].…”
Section: Introductionmentioning
confidence: 99%